2021
DOI: 10.1039/d1ee00074h
|View full text |Cite
|
Sign up to set email alerts
|

Engineering electrocatalyst nanosurfaces to enrich the activity by inducing lattice strain

Abstract: Electrocatalysis undeniably offers noteworthy improvements to future energy conversion and storage technologies, such as fuel cells, water electrolyzers, and metal–air batteries. Molecular interaction between catalytic surfaces and chemical reactants produces...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
94
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 149 publications
(94 citation statements)
references
References 174 publications
0
94
0
Order By: Relevance
“…Similar activity enhancement strategies by strain engineering can be applied generally under the alkaline conditions. 112 …”
Section: Alkaline Hydrogen Evolution Reactionmentioning
confidence: 99%
“…Similar activity enhancement strategies by strain engineering can be applied generally under the alkaline conditions. 112 …”
Section: Alkaline Hydrogen Evolution Reactionmentioning
confidence: 99%
“…Strain effect has been actively studied to stimulate the inactive surfaces of various catalysts. [ 13 ] By modulating the atomic distances to generate lattice strain, the d‐band center will be shifted, which can optimize the chemisorption, and in turn improve the catalytic performance. [ 14 ] Structural defect is an important source of lattice strain, [ 13 ] and surface reconstruction has been commonly used to introduce structural defect, [ 15 ] especially in electrocatalysis.…”
Section: Introductionmentioning
confidence: 99%
“…[13] By modulating the atomic distances to generate lattice strain, the d-band center will be shifted, which can optimize the chemisorption, and in turn improve the catalytic performance. [14] Structural defect is an important source of lattice strain, [13] and surface reconstruction has been commonly used to introduce structural defect, [15] especially in electrocatalysis. However, the lattice strain of noble metal nanomaterials induced by surface reconstruction has rarely been studied.In this work, we introduced lattice tensile strain into Pd NSs by surface reconstruction for nanozyme-based catalytic therapy and dual phototherapy.…”
mentioning
confidence: 99%
“…Generally, the commonality of these approaches is to change the electronic structure of the atomic surface by adjusting or controlling the physical and chemical state of the catalyst surface, so as to simultaneously optimize the binding strength between different reaction intermediates (e.g., *H, *O, *OOH, and *OH) and active sites. Analogously, surface strain engineering has emerged as one of the most promising ways in precisely modulating the electronic configuration and altering binding energies toward adsorbates by the atomic‐scale structural deformation effects (lattice compressive or tensile strain) 15–26 . Recent studies have shown that the lattice strain can be maximized to tailor the d‐band orbital overlap and significantly alter the Gibbs adsorption/desorption free energy for reactive intermediates by modifying the distance between atoms, and thus efficiently stimulate the intrinsic activity of the catalyst in various electrochemical reactions (e.g., HER, OER, and ORR) 15–19,27–32 .…”
Section: Introductionmentioning
confidence: 99%